2018
DOI: 10.1111/jam.13695
|View full text |Cite
|
Sign up to set email alerts
|

Influence of spore and carrier material surface hydrophobicity on decontamination efficacy with condensing hydrogen peroxide vapour

Abstract: The intensity of spore inactivation depends more on other factors than on the wettability of the bacterial spores. However, hydrophobic surfaces lead to faster inactivation effects and should thus be preferred for aseptic packaging technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The findings indicated that surface tension of the condensate can prevent the homogeneous wetting of the surface. [ 132 ]…”
Section: Chemical Sterilizationmentioning
confidence: 99%
“…The findings indicated that surface tension of the condensate can prevent the homogeneous wetting of the surface. [ 132 ]…”
Section: Chemical Sterilizationmentioning
confidence: 99%
“…Water contact angle measurement of four different CMs was carried out as described above. The results were already published in Eschlbeck et al (2018). The chosen materials and the respective surface hydrophobicity are depicted in Table 1.…”
Section: Carrier Materialsmentioning
confidence: 99%
“…Water contact angle data of the applied CMs and bacterial spores were already published in Eschlbeck et al (2018). For a better understanding of the influence of surface hydrophobicity on the inactivation with gaseous H 2 O 2 , the results are depicted in Figure 1.…”
Section: Surface Hydrophobicity Of Cmsmentioning
confidence: 99%
See 2 more Smart Citations